PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN KECEMASAN PRIMIGRAVIDA PARTURIEN KALA I FASE LATEN DAN LAMA PERSALINAN - solihah, rosida; Sastramihardja , Herri S; Suardi, Achmad (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2020)
The rate of maternal mortality in Indonesia has been more increasing. One of them is caused by prolongation of birth. It is occured by some factors. They are parity, interval of birth, age, premature rupture of membranes (KPD), dependent women, anxiety, fear, response and stress. One of the ways that can be used to overcome the anxiety is by giving spiritual emotional freedom technique (SEFT) treatment on parturien. The objective of the research is to find out the influence of SEFT treatment on anxiety reduction primigravida parturien I latent phase and the duration of birth. The research uses Quasi Eksperimental methode by involving the sample 26 infartu mothers as a pretest-postes control group design. The research was conducted from November-January 2018. Sampling in the research uses concecutive sampling so that the researcher obtained 13 respondents treatment group and 13 respondents for control respondents. The results of the research in the intervention group showed decrease in anxiety score from pre to post with thitung result of 5,944 with a p value 0.000. In the variable of prolongation birth showed there was a difference between the intervention group and the control group with the thitung of -8.830 with a p value of 0.000, whereas the results of different test in both groups on the decrease in anxiety on the duration of birth showed the value of p 0.001, which means there is the effect of SEFT on decrease anxiety primigravida parturien 1 latent phase and duration of birth.